2019
DOI: 10.21831/hej.v1i2.23288
|View full text |Cite
|
Sign up to set email alerts
|

Pembuatan Tempe Bekatul Dan Kandungan Gizinya

Abstract: Penelitian bertujuan: 1) mengetahui formula tempe bekatul yang tepat sesuai dengan karakteristik bekatul, 2) mengetahui daya terima konsumen terhadap tempe bekatul, dan 3) mengetahui kandungan gizi tempe bekatul berdasarkan analisis proksimat. Jenis penelitian adalah eksperimen di Laboratorium Program Studi Pendidikan Teknik Boga, Universitas Negeri Yogyakarta dan Chemix Pratama. Disain penelitian adalah rancangan blok lengkap 3 kali ulangan percobaan dan 2 kali sampel. Formula tempe bekatul 1 dan 2 menggunaka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Hazard et al, (2013) [39] reported that soil pH has a marked effect on AMF communities in agroecosystems and crops, and Deepika and Kothamasi (2015) [40] reported that higher moisture content significantly reduced the diversity of AMF. In the case of oil palm, a positive correlation between AMF biodiversity and pH is reported [37]. Considering this information, the lower soil pH and higher moisture content in SPS might reduce the diversity of AMF species, resulting in the lower number of clades distribution in SPS compared to MS in this experiment (Figure 3).…”
Section: Amf Community Structurementioning
confidence: 61%
See 1 more Smart Citation
“…Hazard et al, (2013) [39] reported that soil pH has a marked effect on AMF communities in agroecosystems and crops, and Deepika and Kothamasi (2015) [40] reported that higher moisture content significantly reduced the diversity of AMF. In the case of oil palm, a positive correlation between AMF biodiversity and pH is reported [37]. Considering this information, the lower soil pH and higher moisture content in SPS might reduce the diversity of AMF species, resulting in the lower number of clades distribution in SPS compared to MS in this experiment (Figure 3).…”
Section: Amf Community Structurementioning
confidence: 61%
“…and Acaulospora spp. are dominant in the soil of oil palm plantations in Thailand [37], and Glomus spp. were dominant in date palm [38].…”
Section: Amf Community Structurementioning
confidence: 99%
“…Lemak bekatul mencapai 10-20 g/100 g dengan keunggulan mampu menurunkan kolesterol. Bekatul juga merupakan sumber serat pangan (dietary fiber) yang sangat baik, selain untuk memperlancar proses pencernaan, serat pangan juga berpengaruh terhadap penurunan kadar kolesterol darah (14).…”
Section: Pendahuluanunclassified
“…Serat pada bekatul yang tinggi menyebabkan tekstur kasar pada es krim. Auliana (2011) menyebutkan jumlah kandungan serat pada bekatul sebesar 12%.…”
Section: Teksturunclassified